Ioane Minchkhi - Georgian Hymnographer of the 10th Century - Lela Khachidze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2014)
In this paper, important aspects of the legacy of the most prominent 10th century Georgian hymnographer – Ioane Minchkhi are discussed. Certain issues of Ioane Minchkhi’s creative activity were partially studied by Georgian scholars. As part of this comprehensive research into Minchkhi’s creative works, the unexplored part of his creations – 77 hymns revealed by us are of special interests. The study of this unknown heritage redefined Ioane Minchkhi’s place in the history of Georgian literature. At the same time, the standards and importance of Georgian original hymnography were presented in a new way. Minchkhi’s hymns are perfect examples of Georgian hymnography. Along with great traditionalism Minchkhi’s creative works are characterised by great originality. It is the combination of these two factors that makes Minchkhi’s works impressive and secures their special place in the history of Georgian hymnography. As seen, Minchkhi was an editor and compiler of the first Georgian Lenten Triodion – one of the most important liturgical – hymnographical collections. It laid the foundation to the following editions of this collection. Minchkhi introduced new verse metres and new melodies into Georgian hymnography. Minchkhi’s great contribution to the history of Georgian church and literature is most fully expressed by George the Athonite – the greatest authority of the Georgian church, an outstanding scholar of Georgian and Byzantine writing.